Myelodysplastic syndromes - Szymała, Katarzyna; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2003)
The myelodysplastic syndromes (MDS) are a heterogeneous group of acquired, clonal hematopoietic system diseases characterized by ineffective hematopoiesis and dysplastic changes of bone marrow and peripheral blood cells. The bone marrow is usually hyperplastic with one, two or pancytopenia in peripheral blood. The myelodysplastic syndromes occur mainly in advanced age patients. The majority of MDS cases are the primary disorders with unknown etiology, but the number of secondary MDS, caused by earlier antineoplastic therapy, has been growing lately. Etiopathogenesis of MDS is complex and not entirely recognized. The investigations about cytogenetic disorders, regulation of hematopoiesis and apoptosis are still in progress. The myelodysplastic syndromes with variable rates and frequencies evolve to the acute myelotic leukemia (AML). MDS and AML are considered now as parts of the same continuous disease. The WHO classification of MDS considers RAEB-t to be AML and also eliminates CMML which is included among myelodysplastic- -myeloproliferative diseases. The drawback of the new classification is the lack of clinical characteristic and prognostic relevance of the particular types of MDS. Prognosis in MDS is evaluated on the basis of marrow blast percentage, karyotype and degree of cytopenia. These variables have the strongest correlation with the median survival and risk of transformation to AML. Using these data and taking into consideration the age of patients the International Prognostic Scoring System for Evaluating Prognosis (IPSS) in MDS was formulated and it is the basis for making the decision on the therapy and gives possibilities to compare the effects of treatment methods.